The Factors Affecting the Development of Advertising through Social Media to Influence the Sport Product Customers’ Behavior Intentions - Ali Karimi; Peyman Akbari (Sports Business Journal)
Purpose: Social media has influenced individuals' need for interpersonal interactions. The study was conducted to identify and prioritize the factors affecting advertising development through social media to control customers' intentions for sports products.Methodology: The research method (in the qualitative part of the Delphi method and the quantitative descriptive-analytical part). The statistical population of the qualitative section included all media management specialists and sports marketers, and in the quantitative section, there were athletes of different sports (N = 1600). Sampling was also purposeful and accessible. The study tool was a semi-structured interview and a researcher-made questionnaire derived. Systematic coding and confirmatory factor analysis with SPSS24 and Amos25 software have been used to analyze the data.Findings: If marketers want to change people's mindsets, advertising messages should be clear about the product's benefits and examine customers' characteristics. This causes consumers to change their existing beliefs. Based on the results of the factors affecting the development of advertising through social media to influence customers' behavior intentions for sports products, priority includes individual factors, branding, accreditation, and structural factors.Originality: In this article, we examine the modeling of advertising development through social media to influence customers’ behavioral intentions for sports products using structural equation modeling (SEM).